Human Resource Transformation: A Change Approach and Management Flexibility During the Covid-19 Pandemic - Achmad Sholihin (UIN Raden Mas Said Surakarta, 2022)
Change management is a structured approach that is used to help employees individually and in teams in transition to new and better conditions. Likewise with the application of flexible management, which is adaptive to drastic changes in socio-economic conditions that directly affect the management of the company. For this reason, human resources transformation is a critical step to be implemented immediately to secure the company in times of crisis due to the Pandemic. Quantitative research that takes a sampling of employees of the food company PT. Aerofood Indonesia examines the process of human resources transformation through a change approach and flexibility. Through cluster analysis, employees can be grouped into five characteristics which at the same time describe the condition of human resources transformation. The clustering analysis that tested the correlation through chi square analysis obtained a probability value of less than five percent, thereby proving that the change management and management flexibility implemented by the company during the Pandemic had a correlation with human transformation in all groups who had the same perspective on changes and flexibility of company management.